Rekonstruksi Hukum Keluarga Islam di Pakistan dalam Menjawab Tantangan Kontemporer Masyarakat Muslim: Rekonstruksi Hukum Keluarga Islam di Pakistan dalam Menjawab Tantangan Kontemporer Masyarakat Muslim - adellia essa; Rida Aryani; Muhammad Jaidi (Institut Agama Islam Darul Ulum Kandangan, 2026)
The reconstruction of Islamic family law in Pakistan is a crucial step in addressing the contemporary challenges facing Muslim society. Therefore, research is warranted to determine the form of legal reform and the effectiveness of its implementation in social life. Through normative legal research using a qualitative approach and a literature review of legislation, particularly the Muslim Family Laws Ordinance (MFLO) of 1961, as well as related scholarly literature, it is known that the reconstruction of family law in Pakistan was carried out through more systematic regulation of aspects of marriage, polygamy, divorce, maintenance, and inheritance. However, in practice, various irregularities are still found, such as unregistered marriages, polygamy without the permission of the Arbitration Council, and divorces that do not follow established procedures. This condition is driven by low public legal awareness, the strong influence of patriarchal culture, and differences in understanding of Islamic law. This in turn has resulted in injustice in family relationships, particularly for women and children. Therefore, the reconstruction of Islamic family law in Pakistan has not been fully effective. Strengthening legal implementation, increasing public awareness, and an active role for the state in ensuring justice and well-being in family life in contemporary Muslim society are necessary.